Government Policy Against Unemployment Due to Termination of Employment - Ida Hanifah (International Journal Reglement & Society (IJRS), 2021)
The number of unemployed nationally is of course influenced by the number of unemployed in the regions, both in urban and rural areas. The availability of relatively limited employment opportunities is unable to absorb job seekers who continue to increase every year in line with the increase in population. The high unemployment rate does not only cause problems in the economic field, but also various problems in the social field, such as poverty and social insecurity. The problem of the availability of employment opportunities in Indonesia has now reached a fairly alarming condition, marked by a large number of unemployed and relatively low incomes. Unemployment can be a burden on families and communities, a major source of poverty, can encourage increased social unrest and crime, and can hinder development in the long term. The bad impact of unemployment is the reduced level of people's income which in turn reduces the level of prosperity/welfare. The procedure used to collect data in this study is documentation, namely the guidelines used in the form of notes or quotes, searching legal literature, books and others related to the identification of problems in this study both offline and online. Analysis of legal materials is carried out using the content analysis method (centent analysis method) which is carried out by describing the material of legal events or legal products in detail to facilitate interpretation in the discussion. The concept of labor itself is defined as a population of working age who is ready to do work, namely 15-65 years of age. According to Law No. 13 of 2003, labor is anyone who is able to do work to produce goods and services, both to meet their own needs and those of others or the community. In this case, the workforce is grouped into Educated Workers, namely workers who require a high level of education. For example, doctors, teachers, engineers, etc., trained workforce is a workforce that requires training and experience. For example, drivers, mechanics, etc., uneducated and trained workers are workers who do not require prior education or training in their work. For example, sweepers, garbage collectors, etc. Based on Article 150 of Law Number 13 of 2003 concerning Manpower, it is stated that